2022
DOI: 10.1007/s10433-022-00692-4
|View full text |Cite
|
Sign up to set email alerts
|

A social exclusion perspective on loneliness in older adults in the Nordic countries

Abstract: Several factors associated with loneliness are also considered indicators of social exclusion. While loneliness has been proposed as an outcome of social exclusion, there is limited empirical evidence of a link. This study examines the associations between social exclusion indicators and loneliness in older adults (60+ years) in four Nordic countries. Data from four waves of the European Social Survey were pooled, providing a total of 7755 respondents (Denmark n = 1647; Finland n = 2501, Norway n = 1540; Swede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
(55 reference statements)
2
17
0
Order By: Relevance
“…Loneliness refers to the negative emotional reaction to the difference between one’s anticipated and actual social relationship ( Peplau and Perlman, 1982 ; Vanhalst et al, 2015 ). Previous research has demonstrated that some indicators of social exclusion (such as lower frequency of social contacts and lack of emotional support) can significantly and positively predict loneliness experiences ( Dahlberg et al, 2022 ). Prior scholars also proved that social exclusion has a strong impact on students’ loneliness as well as other mental health problems ( Arslan, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness refers to the negative emotional reaction to the difference between one’s anticipated and actual social relationship ( Peplau and Perlman, 1982 ; Vanhalst et al, 2015 ). Previous research has demonstrated that some indicators of social exclusion (such as lower frequency of social contacts and lack of emotional support) can significantly and positively predict loneliness experiences ( Dahlberg et al, 2022 ). Prior scholars also proved that social exclusion has a strong impact on students’ loneliness as well as other mental health problems ( Arslan, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The share of lonely older adults was higher in previous research than in the present context, including in Finland and Sweden [1]. However, it should be noted that we assessed the experience of suffering from loneliness instead of frequent loneliness.…”
Section: Discussionmentioning
confidence: 59%
“…In response to the COVID-19 pandemic, Sweden and Finland imposed several measures to prevent COVID-19, with different levels of intensity and varying recommendations and legislative measures [16,17]. Although loneliness is highly influenced by individual-level characteristics and resources, it is also affected by policy measures and contextual features, including for example how loneliness is presented in the public discourse, potentially explaining the observed regional differences in 2021 [1]. Future research should focus more on policy and the structural impacts on loneliness, a research field that is still relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, some of the mothers in their study expressed that nonsupport increased the depression they experienced. A lack of emotional support has been linked to greater feelings of loneliness in Norway (Dahlberg et al, 2022); it has also been found to increase irritation and decrease satisfaction in Japanese married couples, particularly for wives (Suzuki, 2007).…”
Section: Nonsupportmentioning
confidence: 99%